A Simulation-Based Resource for Improving Patient Safety and Improving the Patient Experience - Warren Upson Otis; Lynn Sweeney; Adam Rojek; David Lindquist (Association of American Medical Colleges, 2013)
Abstract This simulation-based resource is designed to increase patient safety and improve the patient experience through standardized communication between staff members and between staff and patients. It teaches the principles of Crew Resource Management (CRM) and a service-focused patient care environment using a Structured Patient Encounter (SPE). It uses a simulation-based teaching format with a series of three cases. The medical care and decision-making involved with these cases is straightforward. The focus of these simulations should not be on the medical care, but should be on the principles of CRM and refining the patient experience using the SPE. These cases are intended for a multidisciplinary team of staff members that include techs, nurses, and physicians. This module was taught to 70 physicians (residents and attendings) and 143 nurses and support staff. Surveys were administered to trainees before and after training that assessed two key components: (1) the quality of communication between staff members and (2) the quality of the communication between staff and patients. We found significant improvement in staff's perception of the quality of communication between staff members and with patients and family.